Serve the People!: Corporate Social Responsibility (CSR) in China - Mads Holst Jensen (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2006)
Taking into account a broad range of stakeholders who may affect or be affected by corporate action, the perspective of Corporate Social Responsibility (CSR) carries the promise of a win-win situation for all. CSR in China is highly topical, as the country is integrating into the supply chains of the major global players, but the ideals of CSR are a far cry from the realities of production in "the workshop of the world". In this paper I will discuss key issues relating to the process of adapting CSR into the Chinese context. I will focus on the position of the PRC political leadership. I argue that the leadership seems to pursue an agenda of submerging CSR under the control of the Party-State and conceptualizing CSR by reference to a blend of an eclectic interpretation of Western European welfare models and CSR conceptions with an eclectic interpretation of Chinese tradition and political culture. As a result, CSR in China lacks the element of multi-stakeholder dialogue, which is commonly recognized as the core element of CSR in Western countries. Keywords: CSR, China, Labour issue, MNCE, NGO, Politic change.
hdl:10398/7405
Keywords: 330